Impact of paralympic sports on the resilience of people with disabilities: evaluation and key analysis - Karollyni Bastos Andrade Dantas; Gabriel Gastélum-Cuadras; David Arnoldo García-Fernández; Francisco Prado Reis; Estélio Henrique Martin Dantas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: The aim of this study was to compare the degree of resilience in people with motor disabilities, both those who do and do not practice para-sports.